Should we use conventional or functional performance measures for evaluation of immediate outcomes after TKA? - Amarase, MD, Chavarin; Tanavalee, MD, Aree; Veerasethsiri, MD, Pathomporn; Ngamukos, MD, Srihatach (Journal of Southeast Asian Orthopaedics, 2022)
Introduction: Recently, evaluation of outcomes following total knee arthroplasty (TKA) in the immediate postoperative period (≤ 12 weeks) has been frequently reported for efficiency of new surgical approaches or new pain management protocols. Several functional performance measures have been added to those of conventional tools. However, there has been no comparative evaluation of individual measures at a serial follow-up for immediate outcomes after TKA, in terms of time to significant improvement compared the preoperative period. Methods: We prospectively evaluated 40 patients who had primary knee osteoarthritis and underwent uncomplicated TKA for immediate outcomes at postoperative 2nd week, 6th week, and 12th week, consecutively. All patients were evaluated for conventional outcome measures, including Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) index and SF-36, as well as functional performance measures, including Time up and go test (TUGT) and 6-min walk distance (6MWD). The improvement of individual tests at each evaluation was compared to the preoperative period. Results: There were 37 females and 3 males. The patients’ mean age was 70.1 years, and mean body mass index (BMI) was 27.26 kg/m2. The majority of patients (97.5%) had ASA class I and II. At the 2nd week, several conventional measures, including WOMAC index and SF-36 provided significant improvement; however, all of the functional performance measures showed significantly worse parameters than those at the preoperative evaluation. Functional performance measures, including TUGT and 6MWD provided significant improved outcomes at the 12th week. Conclusion: Conventional measures demonstrated faster outcome improvements after TKA than function performance.